Cerebral Venous Sinus Thrombosis in Preterm Infants. Issue 7 (15th April 2022) - Christensen, Rhandi; Krishnan, Pradeep; deVeber, Gabrielle; Dlamini, Nomazulu; MacGregor, Daune; Pulcine, Elizabeth; Moharir, Mahendranath
Abstract : Background: Neonatal cerebral venous sinus thrombosis (CVST) can lead to brain injury and neurodevelopmental impairments. Previous studies of neonatal CVST have focused on term infants, and studies of preterm infants are lacking. In this study, we examined the clinical and radiological features, treatment and outcome of CVST in preterm infants. Methods: This was a retrospective, consecutive cohort study of preterm infants (gestational age <37 weeks) with radiologically confirmed CVST. All magnetic resonance imaging/MRV and CT/CTV scans were re-reviewed to study thrombus characteristics and pattern of brain injury. Outcome was assessed by the validated pediatric stroke outcome measure at the most recent clinic visit. Results: Twenty-six preterm infants with CVST were studied. Of these, 65% were moderate-late preterm (32–37 weeks), 27% very preterm (28–32 weeks), and 8% extreme preterm (<28 weeks). Most (73%) were symptomatic at presentation with seizures or abnormal exam. Transverse (85%) and superior sagittal (42%) sinuses were common sites of thrombosis. Parenchymal brain injury was predominantly periventricular (35%) and deep white matter (31%) in location. Intraventricular hemorrhage occurred in 46%. Most infants (69%) were treated with anticoagulation. No treated infant (including eleven with pretreatment hemorrhage) had new or worsening post-treatment hemorrhage. Outcomes ranged from no deficits (50%), mild-moderate (25%), and severe (25%) impairment. Conclusions: In our sample of preterm infants with CVST, more than one-quarter were asymptomatic. White matter brain lesions predominated and one-half had neurological deficits at follow-up. Anticoagulation of preterm CVST in this small cohort appeared to be safe. Larger studies of preterm CVST are needed.